TRANSFORMASI PENDIDIKAN YANG MEMBENTUK BANGSA YANG TERDIDIK - Arnoltus, Cornelius (Jurnal Euntes, 2023)
Abstract: John Dewey expressed his understanding of education as a process of experience. Also in some quotes wise words say that experience is the best teacher. Education is important for every individual. Individuals need education to be able to develop, both physically/biologically, psychologically, knowledge, etc. Good education will have a good impact on the recipient of education. The world of education is always changing and developing. Indonesia has experienced at least 9 curriculum changes. Of course this is not without causes for these changes, but there are big things behind these changes. Curriculum transformation is like a double-edged sword. Each has advantages and disadvantages. But apart from that, this paper briefly discusses curriculum transformation. Keywords: Curriculum, Education, Educational Development